Biomarker Testing to Estimate Under-Reported Heavy Alcohol Consumption by Persons with HIV Initiating ART in Uganda - Hahn, Judith A.; Bwana, Mwebesa B.; Javors, Martin A.; Martin, Jeffrey N.; Emenyonu, Nneka I.; Bangsberg, David R. (AIDS and Behavior, 2010)
Alcohol affects the transmission and treatment of HIV, yet may be under-reported in resource-limited settings. We compared self-reported alcohol consumption with levels of plasma carbohydrate-deficient transferrin (%CDT), a biomarker of heavy alcohol consumption, in persons initiating antiretroviral therapy in Uganda. Almost seven percent (6.7%) of persons reporting abstaining and 10% reporting consuming 1–40 drinks in the prior month tested positive for %CDT, and actual under-report may be higher due to low sensitivity of %CDT. These results suggest likely under-report in those reporting abstaining and current drinking. Improved identification of heavy alcohol consumption is needed for research and clinical purposes.
Keywords: Carbohydrate-deficient transferrin; Biological markers; Alcohol drinking; HIV; Antiretroviral therapy; Uganda